Frequency of etiologies of acute kidney injury in Faisalabad and surrounding districts - Farid, Muhammad A.; Khan, Rizwan R.; Azhar, Salman; Saqib, Ali; Ahmad, Imran N.; Baig, Muhammad W. (International Journal of Research in Medical Sciences, 2019)
Background: To find out the causes of Acute Kidney Injury (AKI) in population. Methods: A total of 150 patients were enrolled from medical, surgical, gynecology and obstetrics units of Allied Hospital and Madinah Teaching Hospital, Faisalabad, Pakistan. History, physical examination and investigations were recorded on specially designed proforma. Patients were evaluated to find out the etiologies of AKI. All patients were subjected to urine analysis, complete blood count, blood biochemistry (urea, creatinine, electrolytes, uric acid, calcium and phosphorus) and ultrasound scan of the abdomen and pelvis. Renal biopsy, immunological assays, such as hepatitis B surface antigen, anti-hepatitis C virus antibody, complements level, antinuclear antibody, anti-double-stranded DNA, anti-neutrophil cytoplasmic antibody and anti-glomerular basement membrane antibody were performed in selected cases. Results: Male (36%) and female (64%). Pre-renal AKI was most common and was reported in 80 patients (53.33%). Intrinsic Renal azotemia in 56 patients (37.33%). Post renal azotemia in 14 patients (9.33%). Among 80 patients of prerenal AKI, hemorrhage in 45(56.25%), gastroenteritis in 16(20%), sepsis in 8(10%), cardiac diseases in 4(5%), hepatorenal syndrome in 3 (3.75%), peritonitis in 2 (2.50%) and burns in 2(2.50%) were the main causes of Pre-renal AKI. Among 56 patients of intrinsic renal AKI, 40(71.4%) had acute tubular necrosis (ATN), 12(21.4%) with multifactorial causes and 4(7.14%) were found to have glomerulonephritis. Among 14 patients of post renal AKI, 6(42.9%) were having calculi, 6(42.9%) were to have enlarged prostate and 2(4.3%) were having stricture urethra. In this study, contribution of obstetrical, medical and surgical etiologies were recorded as 40%, 36% and 20% respectively. Conclusions: In contrast to study reported from neighbouring country, this study shows rather increase in pregnancy related AKI.